2002
DOI: 10.1007/s00442-002-0887-7
|View full text |Cite
|
Sign up to set email alerts
|

The fate of nitrogen in gypsy moth frass deposited to an oak forest floor

Abstract: Forest defoliation by insects can lead to severe disruptions of the nitrogen (N) cycle resulting in elevated NO levels in stream water. To trace the movement of insect-mobilized N in a forest soil, N-labeled gypsy moth frass orN-labeled oak leaf litter was added to trenched plots in an oak forest over 29 months. Nitrogen movement from the frass or litter was measured in the available, mineralizable, microbial and total soil pools. Uptake of N by oak seedlings and inorganic N leaching losses were also measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 32 publications
6
49
0
Order By: Relevance
“…1b), particularly when observed relative to added substrate N (frass = 17%, litter = -8% (less than control), Table 2). Interestingly, the time-series of ammonium-N concentrations ( Figure S2) suggested quite strong and rapid immobilisation capacities in all treatments (except the control), which is in line with most findings from temperate forests that suggest a temporal and spatial redistribution of N due to insect herbivory rather than a net loss from the system (Lovett and Ruesink 1995;Christenson et al 2002;Lovett et al 2002;Hunter 2007, 2008). This may be explained by lower N mineralisation rates in the frass ?…”
Section: Discussionsupporting
confidence: 85%
“…1b), particularly when observed relative to added substrate N (frass = 17%, litter = -8% (less than control), Table 2). Interestingly, the time-series of ammonium-N concentrations ( Figure S2) suggested quite strong and rapid immobilisation capacities in all treatments (except the control), which is in line with most findings from temperate forests that suggest a temporal and spatial redistribution of N due to insect herbivory rather than a net loss from the system (Lovett and Ruesink 1995;Christenson et al 2002;Lovett et al 2002;Hunter 2007, 2008). This may be explained by lower N mineralisation rates in the frass ?…”
Section: Discussionsupporting
confidence: 85%
“…In our site, apparently, no increase in nitrate production or aluminium and iron mobilization seemed to have occurred, and the low sulfate concentrations in streamwater reflect the high sulfate adsorption capacity of these desaturated soils with high organic matter content (Dambrine et al, 2000). Absence of response in nutrient concentration after insect defoliations was also reported by Bormann and Likens (1979) and Christenson et al (2002) in watersheds covered by other tree species different from E. globulus. The insect defoliation may cause an increase of nitrogen and labile carbon to the forest floor (Rinker et al, 2001;Lovett et al, 2002;Frost and Hunter, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…Increases in NO 3 export have also been observed following gypsy moth (Lymantria dispar) defoliation (Eshleman et al, 1998;Webb et al, 1995). Christenson et al (2002) have shown that the nitrogen comprised within gypsy moth frass can be rapidly immobilized within the soil in northern hardwood stands. Lovett et al (2002) suggested that most of the nitrogen released from foliage through defoliation by the gypsy moth is redistributed within other forest compartments, and that leaching losses are relatively small.…”
Section: Introductionmentioning
confidence: 85%